Stylidium javanicum (Stylidiaceae), a new triggerplant record for the Philippines - Journé, Valentin; Barcelona, Julie F.; Lafrankie, James V.; Pelser, Pieter B. (Phytotaxa, 2014)
Stylidium javanicum, a very poorly known species formerly only recorded from Java, Sumba, and New Guinea, is here reported as a new record for the Philippines, where it was found in grasslands in Antique Province of Panay Island. It is morphologically similar to S. alsinoides, the only other Stylidium species known for the country, but can be distinguished from it by larger flowers, smaller fruits, and more narrowly acute petal apices.